2012
DOI: 10.1007/s11262-012-0740-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and phylogenetic analysis of orf viruses isolated from outbreaks in goats of Assam, a northeastern state of India

Abstract: Two outbreaks of orf virus (ORFV) (a parapoxvirus) infection in goats, which occurred in Golaghat and Kamrup districts of Assam, a northeastern part of India, were investigated. The disease was diagnosed by standard virological and molecular techniques. The entire protein-coding region of B2L gene of two isolates were cloned and sequenced. Phylogenetic analysis based on B2L amino acid sequences showed that the ORFVs identified in these outbreaks were closely related to each other and both were closer to ORFV-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 11 publications
5
36
0
Order By: Relevance
“…Besides, a percent identity of 83.8-83.9 and 83.4 with BPSV isolates whereas, 93.6-95.1 and 94.7-95 with PCPV was observed, at nt and aa levels, respectively. It shares a significant identity of 97.8-98.2 and 97.4-98.4 % with ORFV isolates worldwide for which the complete genome has been sequenced and characterized (IA82, SA00, NZ2 and D1701 isolates) as observed in previous reports [1,18]. Among Asian isolates, ORFV JS/04 of China shared maximum percent identity of 99.4 and 99.2 with this isolate under the study.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Besides, a percent identity of 83.8-83.9 and 83.4 with BPSV isolates whereas, 93.6-95.1 and 94.7-95 with PCPV was observed, at nt and aa levels, respectively. It shares a significant identity of 97.8-98.2 and 97.4-98.4 % with ORFV isolates worldwide for which the complete genome has been sequenced and characterized (IA82, SA00, NZ2 and D1701 isolates) as observed in previous reports [1,18]. Among Asian isolates, ORFV JS/04 of China shared maximum percent identity of 99.4 and 99.2 with this isolate under the study.…”
supporting
confidence: 60%
“…However, the presence of viral nucleic acid in skin tissue was identified by molecular diagnostics namely diagnostic PCR and B2L gene cloning/ sequencing. Multiple sequence alignment and phylogenetic tree based on complete B2L sequence have been performed to study the evolutionary relationship with other circulating virus strains/isolates in the country [1,4,18].…”
mentioning
confidence: 99%
“…The disease is zoonotic and globally prevalent. Orf is enzootic in Indian sheep and goats (Hosamani et al, 2007;Dey and Kundu, 2009;Venkatesan et al, 2011;Yogisharadhya et al, 2012;Bora et al, 2012). Orf is characterized by proliferative and often self-limiting skin lesions including papules, vesicles and rapidly growing scabs on the skin of lips, oral mucosa and around the nostrils.…”
Section: Introductionmentioning
confidence: 99%
“…The envelope gene (B2L) of ORFV encodes a highly immunogenic envelope protein of about 42 kDa. The B2L, DNA polymerase, GIF/IL-2 and VIR genes have been used in studies related to genetic variation and molecular epidemiology [3,12,14,15].…”
mentioning
confidence: 99%
“…The B2L gene based phylogenetic analyses presented here revealed that four species of parapoxviruses (ORFV, PCPV, BPSV, PVNZ) form separate clusters with nucleotide identity levels in the range of 46-95 %. Recently there have been increased reports of CPDV infection worldwide and is enzootic in India [3,12,20]. More recently an outbreak of CPDV infection was reported in Muzzaffarnagari sheep flock of the CIRG, Makhdoom, Mathura, with about 10 % morbidity and no mortality [12].…”
mentioning
confidence: 99%